Difference and relation between balance, physical fitness and quality of life in retired people living in different geographical regions of Turkey (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the relationship and difference between balance, physical fitness and the quality of life in retired people living in different geographical regions of Turkey.Material and Methods: For balance evaluation Berg Balance Scale, for physical fitness evaluation Senior Fitness Test (Chair Stand Test, Arm Curl Test, 2-Minute Step Test, Chair Sit-and-Reach Test, Back Scratch Test and 8-foot Up-and-Go Test) for quality of life evaluation Short Form (36) Health Survey were administered to 155 retired individuals from seven geographical regions of Turkey (Antalya, Gaziantep, Elazığ, Eskişehir, İstanbul, İzmir, Samsun) For statistical analysis, one-way analysis of variance and Spearman’s correlation analysis were used.Results: A total of 155 individuals aged between 55 and over were included in the study. The mean age of the individuals was 64.23±5.86 years. The results of Berg Balance Scale showed statistically significant differences (p0.05) both between balance score and 8-foot Up-and-Go Test scores in Eskişehir and between the balance score and the results of the Arm Curl Test in Antalya (p0.05). There were no significant differences between regions in the results of the SF-36 assessment of quality of life. A significant positive correlation between Berg Balance Scale score and the scores of Chair Stand, Arm Curl and 2-Minute Step Tests was recorded. Furthermore, Berg Balance Score and 8-foot Up-and-Go score were found to present a negative correlation.Conclusion: Aging and differences between geographic regions in which individuals live cause deterioration in balance and this situation effects physical fitness. Although participants had different lifestyles, the fact that our evaluation indicated a lack of difference in the quality of life assessment results was pleasing.Keywords: Aging; balance; physical fitness; quality of life.
Keywords: key.br /Material and Methods: For balance evaluation Berg Balance Scale, for physical fitness evaluation Senior Fitness Test (Chair Stand Test, Arm Curl Test, 2-Minute Step Test, Chair Sit-and-Reach Test, Back Scratch Test and 8-foot Up-and-Go Test) for quality of life evaluation Short Form (36) Health Survey were administered to 155 retired individuals from seven geographical regions of Turkey (Antalya, Gaziantep, Elazığ, Eskişehir, İstanbul, İzmir, Samsun) For statistical analysis, one-way analysis of variance and Spearman’s correlation analysis were used.br /Results: A total of 155 individuals aged between 55 and over were included in the study. The mean age of the individuals was 64.23±5.86 years. The results of Berg Balance Scale showed statistically significant differences (p0.05) both between balance score and 8-foot Up-and-Go Test scores in Eskişehir and between the balance score and the results of the Arm Curl Test in Antalya (p0.05). There were no significant differences between regions in the results of the SF-36 assessment of quality of life. A significant positive correlation between Berg Balance Scale score and the scores of Chair Stand, Arm Curl and 2-Minute Step Tests was recorded. Furthermore, Berg Balance Score and 8-foot Up-and-Go score were found to present a negative correlation.br /Conclusion: Aging and differences between geographic regions in which individuals live cause deterioration in balance and this situation effects physical fitness. Although participants had different lifestyles, the fact that our evaluation indicated a lack of difference in the quality of life assessment results was pleasing.br / Aging; balance; physical fitness; quality of life.